2022
DOI: 10.1111/ctr.14640
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of perioperative analgesia regarding immediate and short‐term outcomes after liver transplantation – A systematic review, meta‐analysis and expert panel recommendations

Abstract: Background: Adequate pain control is essential for patients undergoing liver transplantation (LT). Multiple analgesic strategies have been implemented during the perioperative period. There is no consensus on the optimal perioperative analgesia management.Objectives: To provide recommendations, on the optimal perioperative analgesia management for LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This shift underscores the importance of optimizing postoperative pain management. Such early recovery efforts align with the principles outlined in Enhanced Recovery After Surgery (ERAS) protocols, which have demonstrated potential benefits in improving postoperative outcomes [2]. Table 1 summarizes factors that may influence the analgesic requirements of patients affected by end-stage liver disease (ESLD) undergoing LT [2,8].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This shift underscores the importance of optimizing postoperative pain management. Such early recovery efforts align with the principles outlined in Enhanced Recovery After Surgery (ERAS) protocols, which have demonstrated potential benefits in improving postoperative outcomes [2]. Table 1 summarizes factors that may influence the analgesic requirements of patients affected by end-stage liver disease (ESLD) undergoing LT [2,8].…”
Section: Resultsmentioning
confidence: 94%
“…Ensuring adequate pain control is crucial as it enhances patient comfort and facilitates early mobilization, ultimately contributing to a more rapid overall recovery. Also, respiratory independence is paramount for LT patients, as delayed weaning from mechanical ventilation can adversely impact outcomes [2]. The subcostal incision required for accessing the surgical site can lead to discomfort, especially during activities like deep breathing, coughing, and mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review by Sun et al , this time focusing on deceased donor liver transplant recipients, reviewed nine studies that aimed to provide recommendations on optimal perioperative analgesia management for liver transplant patients [21 ▪▪ ]. The review compared two groups, an opioid cohort and opioid-avoidance cohort, and included interventions such as TEA, TAP block, AWC, hand massage, and multimodal drug regimens.…”
Section: Multimodal Pain Managementmentioning
confidence: 99%
“…[58][59][60] It is strongly suggested that patients with SFSG should be monitored in an ICU environment with regular assessment. Opioid sparing multimodal analgesia should be strongly considered in these patients as part of an ERAS pathway as they have shown to improve short-term outcomes after LT. 61…”
Section: Postoperative Monitoring and Intervention Enhanced Recovery ...mentioning
confidence: 99%